ANTITUBERCULOSIS DRUG SIDE EFFECTS AND MEDICATION ADHERENCE AMONG PATIENTS WITH PULMONARY TUBERCULOSIS: A CROSS-SECTIONAL STUDY AT HUTABAGINDA PRIMARY HEALTH CARE CENTER, NORTH TAPANULI, INDONESIA - Asima Sirait; Evi Sri Junita Sitohang; Vierto Irennius Girsang; Laura Mariati Siregar (Jurnal Ilmiah Keperawatan, 2026)
Background: Non-adherence to treatment remains one of the major barriers to successful pulmonary tuberculosis therapy. The long duration of treatment and the occurrence of antituberculosis drug adverse effects may cause patients to take their medication irregularly or discontinue treatment prematurely. This study aimed to analyze the association between antituberculosis drug adverse effects and treatment adherence among pulmonary tuberculosis patients at Hutabaginda Public Health Center, Tarutung District, North Tapanuli Regency, in 2026. Methods:This observational analytic study used a cross-sectional design. All 73 eligible pulmonary tuberculosis patients receiving antituberculosis drugs in 2026 were included using total sampling. Side effects were assessed using a 13-item questionnaire adapted from previous studies, while treatment adherence was measured using the MMAS-8. Data were analyzed using univariate and bivariate analyses with the Chi-square test. Results:Most respondents experienced mild antituberculosis drug adverse effects, accounting for 60.3%, while 68.5% were categorized as adherent to treatment. Bivariate analysis showed a significant association between antituberculosis drug adverse effects and treatment adherence among pulmonary tuberculosis patients. These findings indicate that the severity of adverse effects experienced by patients is associated with their consistency in undergoing treatment. Conclusion:Antituberculosis drug adverse effects are associated with treatment adherence among pulmonary tuberculosis patients. Easily understood education, adverse-effect monitoring, and continuous support from healthcare workers should be strengthened to help patients complete their treatment.